Public Relations Management in Developing Marketing of Islamic Education Institutions at IIBS Ar-Rohmah Pesantren Putri II Malang - Rikza Ammaziroh; Khairunisyah Abrarrah; Muhammad Amin Nur (STAI Terpadu Yogyakarta, 2024)
Public relations is the most important part of educational institutions, therefore the quality of management and marketing in an educational institution is one of the important factors in the quality assurance indicators of learning and education. Educational institutions have an important urgency in communicating their goals to the community. The role of public relations as a communicator, building a school image, and marketing. This article aims to describe the management of public relations in developing the marketing of IIBS Ar-Rohmah II Putri Malang boarding school. The method used in this research is qualitative with the type of case study. The data collection techniques are interviews with informants, direct presence in the field for observation, and documentation sources from various reports. The results showed that public relations management consists of public relations planning which includes planning ideas with the main elements of market identification and segmentation, targeting, and positioning. Implementation of public relations consists of coordination between the public relations team and the content creator team then implementing activities under the previous plan. Public relations evaluation consists of two phases, namely the unit evaluation phase and the central evaluation.